Soil Seed Bank Dynamics of Pastures Invaded by Navua Sedge (Cyperus aromaticus) in Tropical North Queensland - Chadha, Aakansha; Osunkoya, Olusegun O.; Shi, Boyang; Florentine, Singarayer K.; Dhileepan, Kunjithapatham (Frontiers in Agronomy, 2022)
Navua sedge (Cyperus aromaticus) is threatening crops, pasture species and natural ecosystems in Pacific Island countries and northern Queensland, Australia. To aid future management efforts of this exotic invasive weed, research was conducted to understand the soil seed bank dynamics of pastures invaded by Navua sedge. Six grazing properties were chosen across two landscapes, coastal and inland/upland, with areas that had Navua sedge infestations in Queensland, Australia. At each site, soil was collected from two soil depths, 0-5 and 5-10 cm, and from plots with high and low infestation levels of Navua sedge. It was observed that the soil seed bank dynamics varied significantly between these study sites. Navua sedge was the dominant species in the soil seed bank at all the sites contributing between 62% to 95% of the total seed bank, while pasture seeds occupied only 3% to 24%. Broadleaf seeds were even lower in abundance, showing between 2% to 13% of the total seed count. The abundance of Navua sedge seed present in the soil was significantly correlated with the aboveground biomass of Navua sedge (r=0.53, p=0.006), but no correlation was found with the infestation age of Navua sedge. Based on this work, it is clear that the seed bank of Navua sedge is very large and concentrated within the top 0-5 cm of the soil, with, 83% of total Navua sedge seeds being in this layer. It was also noted that, although, high infestation plots had significantly higher number of seeds than low infestation plots, more than 18,000 Navua sedge seeds/m2 were still found in the 0-5 cm soil layer of plots regarded as low infestation. We suggest that insights achieved from our soil seed bank study may be used to devise management strategies to minimise the impact of Navua sedge weed in critical grazing and agricultural areas.